New Product Innovation with Multiple Features and Technology Constraints - Paulson Gjerde, Kathy A.; Slotnick, Susan A.; Sobel, Matthew J. (Management Science, 2002)
We model a firm's decisions about product innovation, focusing on the extent to which features should be improved or changed in the succession of models that comprise a life cycle. We show that the structure of the internal and external environment in which a firm operates suggests when to innovate to the technology frontier. The criterion is maximization of the expected present value of profits during the life cycle. Computational studies complement the theoretical results and lead to insights about when to bundle innovations across features. The formalization was influenced by extensive interviews with managers in a high-technology firm that dominates its industry.